Pengaruh ketidakpastian lingkungan terhadap partisipasi penganggaran dan kinerja manajerial - Isti Rahayu (Accounting Department, Faculty of Business and Economics, Universitas Islam Indonesia, 1999)
The study attemps to examine the relationship between budgetary participation and individual performance. In so doing the study considers environmental uncertainty as a moderating variable.Data for this study were collected by using questionaires, which were mailed to 430 department managers chosen from Indonesian Capital Markets Directory. There were 81 responses of which 73 were complete and hence usable.The study concludes that the budgetary participation effects the individual performance. However environmental uncertainty did not moderate the effects of participative budgeting on individual performance.